2017
DOI: 10.3201/eid2307.170310
|View full text |Cite
|
Sign up to set email alerts
|

MERS-CoV Antibody Responses 1 Year after Symptom Onset, South Korea, 2015

Abstract: We investigated the kinetics of the Middle East respiratory syndrome coronavirus (MERS-CoV) neutralizing and spike protein antibody titers over the course of 1 year in 11 patients who were confirmed by reverse transcription PCR to have been infected during the outbreak in South Korea in 2015. Robust antibody responses were detected in all survivors who had severe disease; responses remained detectable, albeit with some waning, for <1 year. The duration of viral RNA detection (but not viral load) in sputum sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
248
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(279 citation statements)
references
References 17 publications
27
248
2
2
Order By: Relevance
“…Although the number of asymptomatic patients was limited to 3 in the present analysis, it is less likely that asymptomatic patients will experience seroconversion considering that even Group 1 patients with obvious MERS-related symptoms showed low seroconversion rate of 60%. This finding correlates with another serologic study that evaluated 11 rRT-PCR-confirmed MERS patients (Choe et al, 2017). In that study, antibody titers in 4 of 6 patients with mild illness were undetectable.…”
Section: Discussionsupporting
confidence: 87%
“…Although the number of asymptomatic patients was limited to 3 in the present analysis, it is less likely that asymptomatic patients will experience seroconversion considering that even Group 1 patients with obvious MERS-related symptoms showed low seroconversion rate of 60%. This finding correlates with another serologic study that evaluated 11 rRT-PCR-confirmed MERS patients (Choe et al, 2017). In that study, antibody titers in 4 of 6 patients with mild illness were undetectable.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have demonstrated PCR-positive patients with mild disease often do not produce detectable levels of antibodies, particularly when followed past the acute phase of the disease. 44…”
Section: Histopathologic Featuresmentioning
confidence: 99%
“…Asymptomatic individuals were less likely to have underlying condition (42%) compared to 86% of fatal cases [45]. However, serologic evaluation of contacts and patients may underestimate the extent of the disease as antibodies wane over time and is related to disease severity [46]. Of particular interest is that most of the identified pediatric cases were asymptomatic with no clear explanation [38][39][40]47].…”
Section: Extent Of Asymptomatic Mers In Humansmentioning
confidence: 99%